Knowledge of Tuberculosis Prevention Across Eight Districts in Central Uganda: An Analysis of Lot Quality Assurance Sampling Survey Data - Anguyo ROD; Mukama SC; Bindeeba DS; Senyimba C; Ezajobo S; Nakawesi JS; Mugisa A; Nakubulwa SK; Namitala E; Mulebeke R; Karamagi Y; Katongole SP (Risk Management and Healthcare Policy, 2025)
Robert Onzima DDM Anguyo,1 Semei Christopher Mukama,2 Dedrix Stephenson Bindeeba,2 Catherine Senyimba,2 Simons Ezajobo,2 Jane Senyondo Nakawesi,2 Andrew Mugisa,2 Susan Kiwanuka Nakubulwa,2 Eve Namitala,2 Ronald Mulebeke,2 Yvonne Karamagi,2 Simon Peter Katongole3 1Department of International Public Health, Liverpool School of Tropical Medicine, Uganda (LSTM-Uganda), Kampala, Uganda; 2Mildmay Uganda, Kampala, Uganda; 3Department of Public Health, Gudie University Project, Kampala, UgandaCorrespondence: Robert Onzima DDM Anguyo, Email ranguyo@yahoo.co.ukPurpose: This study assessed tuberculosis (TB)-related knowledge among people of different demographic groups that is essential for effective TB program planning and implementation.Materials and Methods: We conducted a cross-sectional study using the lot quality assurance sampling (LQAS) methodology in 8 districts, stratifying each district into five supervision areas (SAs). We randomly sampled 19 villages from each SA using probability proportional to size (PPS). We interviewed 2280 respondents, including 760 each of youth 15– 24 years, women 15– 49 years and men 15+ years. The data were analyzed in proportions and SA-level classifications using the LQAS-based decision rules.Results: The findings underscore variations in TB knowledge across demographic groups. Among youths, knowledge of at least two TB symptoms stood at 48.6%, while among women and men, it was 55.3% and 57.0%, respectively. Awareness of TB curability was 75.6% among youths, 80.2% among women, and 84.6% among men. A notable proportion of youths (83.4%), women (89.5%), and men (91.4%) were aware of the potential coexistence of HIV and TB. Concerning actions to take if a family member is suspected of having TB, 89.4% of youth, 92.4% of women, and 57.5% of men were knowledgeable. Knowledge of the risks of incomplete TB treatment was noted among 30.9% of youth, 33.0% of women, and 35.0% of men.Conclusion: There is variation in the level of knowledge across different TB thematic areas between demographic groups, districts and sub-districts (SAs). Planners and implementers of TB programs should be cognizant of such variations and make deliberate efforts to develop tailored interventions in order to address the information and/or education needs of specific contexts in order to improve TB outcomes. The findings highlight the need to particularly target the youth with education programs on TB.Plain Language summary: This study assessed how much different groups of people know about tuberculosis (TB).Why was the study done?: The goal was to find out how well people from different age groups and genders understand TB. Understanding this is important for planning and improving TB health programs.What methods did we employ?: We selected 2280 people across eight districts. We divided each district into five sub-divisions and selected 19 villages from each sub-division. From each village, we interviewed one each of youth aged 15– 24, women aged 15– 49, and men aged 15 years or older.What did we find?: Young people who knew about at least two TB symptoms were 48.6%, compared to 55.3% of women and 57.0% of men.Awareness that TB can be cured was 75.6% among youths, 80.2% among women, and 84.6% among men.Most people knew that TB and HIV can occur together: 83.4% of youths, 89.5% of women, and 91.4% of men.About actions to take if someone in their family might have TB, 89.4% of youths, 92.4% of women, and 57.5% of men were aware.Knowledge about the dangers of not finishing TB treatment was lower, with only 30.9% of youths, 33.0% of women, and 35.0% of men aware.Districts have differences in the amount of people who know about the different areas concerning TB.What do these results mean?: People’s knowledge about TB varies by age, gender, and location. TB programs need to consider these differences and create targeted education to improve understanding and control of TB. Planners and implementers of TB programs need to particularly target the youth with education programs on TB.Keywords: tuberculosis knowledge, central Uganda, youth 15– 24 years, women 15– 49 years, men 15+ years